Faktor Harga dalam Strategi Pemasaran Rumah Sakit - Tarigan, Silvia Evalina; Sulistyowati, Retno Dewi; Vandauli, Melanie; Mariani, Mia; Lestari, Petra Ade Paramita Lestari Ade Paramita; Gisella, Prisca (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
One element of a marketing strategy is the marketing mix. Marketing mix is growing, especially in the service sector, not only covering 4P, but including 7P. The 7P concept consists of (product, price, place, promotion, people, process, and physical environment) that is used to make decisions in making marketing communication strategies. In this literature study, particular will be discussed related to price factors in hospital marketing strategies. This literature study uses analysis methods from various sources such as textbooks, journal reference books and e-books related to price factors in hospital marketing strategies. Pricing is classified based on three approaches, including cost oriented pricing, demand oriented pricing, and competition oriented pricing. There are four pricing strategies in marketing, namely premium strategy, over charging strategy, good value strategy, and economic strategy. Company pricing decisions can be based on marketing objectives, marketing mix strategies, and costs.